CHOLERA RESEARCH LANDSCAPE IN NIGERIA, 2010-2025: A SCOPING REVIEW - Elimian, Kelly; Ohize, Stephen (FUDMA Journal of Sciences, 2026)
Nigeria is one of the countries most affected by cholera in sub-Saharan Africa, experiencing recurrent outbreaks despite ongoing prevention and control efforts. Although numerous studies have examined various aspects of cholera in Nigeria, no study has systematically examined the characteristics, evolution, and gaps in the national cholera research landscape. This research aimed to fill this gap. A scoping review was conducted using the Arksey and O'Malley framework and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews guidelines. Literature searches were performed across Web of Science, CINAHL, PsycINFO, Embase, Medline, PubMed and African Journals Online (AJOL) between January 2010 and July 2025. Eligibility was defined as a primary focus on cholera or Vibrio cholerae in Nigeria. Data extraction was performed in Covidence and analysed descriptively. One hundred and fifty-two (152) records met the predefined inclusion criteria.  Of these, the majority were original research articles (83.6%), and over half (57.6%) were published between 2020 and 2025, suggesting significant growth in cholera research activity. Epidemiology (surveillance and laboratory) (11.8%; 18/152), bacteriology/molecular/genomics (5.9%; 9/152), and cross-cutting (61.8%; 94/152) were the most frequently represented thematic areas. However, descriptive and cross-sectional studies dominated the evidence-base. Nearly half of the included studies did not report funding sources. In conclusion, cholera research in Nigeria has expanded considerably over the past 15 years, reflecting national research capacity and scientific attention to the disease; however, there is a dearth of evidence in intervention, implementation, and policy-relevant research.
Keywords: Cholera; research landscape; surveillance; WASH; Nigeria; Vibrio cholerae